Interlanguage Analysis: How morpheme order studies do not necessarily apply to every situation - Muchamad Adam Basori (Journal of English for Academic and Specific Purposes (JEASP), 2022)
Much research on language acquisition, from nativist to interactionist, describes Morpheme Order Studies as a major development in second language acquisition.  This paper intended to discuss how spoken data from a Japanese student could be used to indicate the level of acquisition of English morphemes attained via the processability theory but actually determined that an order of acquisition does not necessarily apply.  Results showed that the informant varied in success in supplying correct morphemes in obligatory contexts, that her first language did not interfere with her second language acquisition and the accuracy of using morpheme order sequence to determine the level of acquisition breaks down because learner’s developmental sequence is unpredictable.